2010
DOI: 10.1007/s00345-010-0617-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of intravesical therapy for non-muscle invasive bladder cancer

Abstract: Long-term outcomes after intravesical therapy for non-muscle invasive bladder cancer are difficult to asses due to the lack of quality long-term data and inconsistencies in reporting results. It is clear that better long-term data are needed to define the impact of intravesical therapy on the natural history of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 82 publications
0
20
0
2
Order By: Relevance
“…The efficacy of these intravesical treatments is limited, and there is debate over both short-and long-term benefits in the recurrence rate in intermediaterisk tumors. [24][25][26] Tumors can also become refractory to treatment, and surgical removal of the bladder (cystectomy) is often needed when current intravesical treatment regimes have been exhausted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of these intravesical treatments is limited, and there is debate over both short-and long-term benefits in the recurrence rate in intermediaterisk tumors. [24][25][26] Tumors can also become refractory to treatment, and surgical removal of the bladder (cystectomy) is often needed when current intravesical treatment regimes have been exhausted.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Additionally, in culture, gemcitabine is selectively toxic to UCB cell lines, suggesting that this treatment might specifically target bladder tumor cells and spare their normal counterparts, reducing overall toxicity. [25][26][27]30,31 Several groups have evaluated the use of gemcitabine as an intravesical treatment for UCB. Bendary et al 31 concluded that gemcitabine had a better safety profile than BCG and was equally as effective in preventing the recurrence and progression of nonmuscle invasive bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…b In Tumorzellen kann sich das Virus jedoch erfolgreich vermehren, was zu einer Lyse der Zelle führt Abb. 2 8 Verschiedene Mechanismen einer Immunantwort nach Virotherapie war die Beobachtung, dass die Kombination von Viro-und Chemotherapie einen synergistischen Effekt aufwies und dabei keine erhöhte Toxizität zeigte [17].…”
Section: Die Virotherapieunclassified
“…Zum Zeitpunkt der Erstdiagnose werden etwa 75% der Blasenkarzinome als nicht-muskelinvasive Tumoren (NMIBC) diagnostiziert, die zwar durch eine geringe Progressionsrate, jedoch Rezidivraten nach 5 Jahren von 80% trotz Therapie charakterisiert sind. Durch die aktuell zugelassenen Therapieformen wird das Auftreten von Rezidiven innerhalb der ersten 5 Jahre nur um etwa 30% gesenkt, eine Verbesserung der tumorabhängigen Progressionswahrscheinlichkeit und damit verbundenen Mortalität konnte bislang jedoch nicht erzielt werden [2,3,4]. Die Gründe für den therapieresistenten Charakter der Tumoren sind außer-ordentlich vielfältig und basieren wahrscheinlich v. a. auf der genetischen Heterogenität dieser Tumorentität.…”
unclassified
“…Response rates are as high as 70% in patients with carcinoma in situ alone. 21 Shelley et al 22 performed a meta-analysis of 6 randomized controlled studies including 585 patients with Ta and T1 disease undergoing TURBT with or without subsequent BCG. This study showed a 70% lower likelihood of recurrence at 1 year in patients receiving BCG.…”
Section: Use Of Bacillus Calmette-guérin In Nmibcmentioning
confidence: 99%